Production Optimization Using Different Scenarios of Gas Lift and ESP Installation - Bataee, Mahmood (Academic Research Online Publisher, 2013)
The production optimization is the key to increase the total production. However, proper production scenario is resulted from the complete reservoir model. The reservoir condition is the clue to find the best production method. This paper had summarized the different studies of gas lift and ESP installation for real field data and compared it with the result of water and gas injection simulation. Different cases of production planning (including new infill wells, modification in reservoir simulation and etc.) had been done for next 40 years of the field life.